GENDER DIFFERENCES IN PATIENTS WITH EPILEPSY CLASSIFIED ACCORDING TO THE INTERNATIONAL LEAGUE AGAINST EPILEPSY CLASSIFICATION - AYAZ, Z; ALI , Z (Biological and Clinical Sciences Research Journal, 2024)
Epilepsy is a neurological disorder characterised by recurrent seizures, and it manifests differently across genders. Understanding these gender differences is crucial for tailored treatment and management strategies. Objective: To determine gender differences in patients with epilepsy classified according to the International League against Epilepsy (ILAE) classification. Methods: This descriptive observational study was conducted at the Department of Medicine, Lady Reading Hospital, Peshawar, from January 2023 to July 2023. The study included 140 patients with epilepsy, comprising 70 males and 70 females aged between 25 to 50 years. Gender differences were examined according to the ILAE classification for epilepsy. Data analysis was performed using SPSS version 23. The Chi-Square test assessed gender differences in epilepsy and its subtypes, with a significance level (p-value) set at < 0.05. Results: The mean age of the participants was 37.74 ± 7.29 years. Idiopathic generalized epilepsy was significantly more common in females (42.9%, n=30) than in males (17.1%, n=12). Cryptogenic localization-related epilepsy was also more frequent in females (48.6%, n=34) compared to males (8.6%, n=6). Conversely, localization-related symptomatic epilepsy was significantly higher in males (74.3%, n=52) than in females (8.6%, n=6) (p = 0.0001). Conclusion: Idiopathic generalized and cryptogenic localization-related epilepsy were more prevalent in females, while localization-related symptomatic epilepsy was more common in males. These findings underscore the importance of considering gender differences in the diagnosis and treatment of epilepsy.